ANALYSIS OF THE EFFECTS OF NONSTEROIDAL ANTI-INFLAMMATORY DRUGS (NSAIDS) IN THE ORAL CAVITY - Gabi Topor; Aurel Nechita; Irina Ruxandra Strambu; Iulian Catalin Bratu; Simona Stefan; Minodora Campanu (Banu); Olimpia Dumitriu-Buzia; Doriana Agop Forna; Simona Parvu (Romanian Journal of Oral Rehabilitation, 2024)
Nonsteroidal anti-inflammatory drugs (NSAIDs) are commonly used for their analgesic and anti-inflammatory effects. However, their prolonged use has been associated with adverse effects on teeth and oral tissues. Studies have shown that NSAIDs can cause oral ulceration, bleeding gums, and delayed healing of lesions in the oral cavity. NSAIDs can also affect bone metabolism, leading to osteonecrosis of the jawbone. In addition, some NSAIDs have been shown to have acidic properties that can cause erosion of tooth enamel and dentin. In dentistry, Drosera sp. has been found to exhibit several pharmacological actions such as analgesic, anti-inflammatory, and antimicrobial properties. The plant contains various phytochemical components, such as flavonoids, alkaloids, and terpenoids, which are responsible for its beneficial effects. These compounds have been shown to possess antioxidant properties, which help reduce oxidative stress and inflammation. Drosera sp. has proven to be effective against tooth decay and periodontal disease. Infections in the oral cavity and caries caused by bacteria of the Streptococcus class are very sensitive to Drosera extracts. This is due to plumbagin, which inhibits the growth and development of strains of Streptococcus mutans, Streptococcus sobrinus, Streptococcus rattus, and Streptococcus cricetus. Studies have also been conducted on pathogens involved in periodontitis and gingivitis caused by Prevotella intermedia, Porphyromonas gingivalis, and Aggregatibacter atinomycetemcomitans.